PENENTUAN WAKTU TANAM PADI GOGO BERDASARKAN NERACA AIR LAHAN DI KABUPATEN ROKAN HULU - Gian Juliano; Besri Nasrul (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Especially in Rokan Hulu Regency, the low productivity of upland rice is caused by the improper planting time. Land dryness often occurs as a result of incorrectly predicting climate which in turn hurts crop yields. This research was conducted to determine the level of groundwater availability based on the analysis of the land water balance and to determine the planting time of upland rice in the Rokan Hulu Regency. The method used in this research is a survey method. The primary data consisted of the water content of field capacity, permanent wilting point, and bulk density. Location of the soil sampling consisted of seven Homogeneous Land Units (SLH) resulted from overlay of soil type map, administrative map, dryland agricultural map using the Geographic Information System technique. Secondary data (climate period 1990-2019) were obtained from Balai Wilayah Sungai Sumatera III. Land water balance analysis was performed using the Thornthwaite-Matter methods. The data obtained were analyzed using descriptive statistics to explain the period of surplus and deficit in groundwater, as well as for determining the planting time for upland rice based on soil water content and plant water needs per growing period at each SLH. The results of the research showed that the Rokan Hulu regency was classified as a wet area with an annual rainfall of 2,751.1 mm (Oldemann C1). Soil water content is classified as very sufficient criteria every month, both topsoil and bottom layer in the range of January-May and September-December. However, in the range of June-August, the soil water content varied at each SLH. Upland rice planting (Inpago Varieties) can be done in January, May, and September in SLH 1, SLH 2, SLH 3, SLH 4, SLH 5, and SLH 6, while in SLH 7 upland rice planting is carried out in January and September. Planting using local varieties can be done in February and September in SLH 1, SLH 2, SLH 3, SLH 4, SLH 5, and SLH 6, while in SLH 7 planting can be done in March and September. Alternating planting can also be done by planting inpago varieties in February and local varieties in September.